2020
DOI: 10.1186/s12916-020-01728-1
|View full text |Cite
|
Sign up to set email alerts
|

Implementation and evaluation of short peripheral intravenous catheter flushing guidelines: a stepped wedge cluster randomised trial

Abstract: Background Peripheral intravenous catheters (PIVCs) are ubiquitous medical devices, crucial to providing essential fluids and drugs. However, post-insertion PIVC failure occurs frequently, likely due to inconsistent maintenance practice such as flushing. The aim of this implementation study was to evaluate the impact a multifaceted intervention centred on short PIVC maintenance had on patient outcomes. Methods This single-centre, inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 26 publications
1
28
0
6
Order By: Relevance
“…We identified some independent factors protecting patients from PIVC failure, including insertion in the forearm with 20 -22 gauge, visual inspection of insertion site, maintenance of transparent polyurethane PIVC dressing and optimal PIVC flushing, all in agreement with published reports 7,23,26,27 . In our study, the overall mean of dressing status was substantially higher for the intervention group compared to the control group at 12 months (66•86 [SD 17 •10] vs 51•37 [SD 25 •26]), a rate comparable to the 64 -79% of dressings in optimal conditions reported previously 13,23,28 .…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…We identified some independent factors protecting patients from PIVC failure, including insertion in the forearm with 20 -22 gauge, visual inspection of insertion site, maintenance of transparent polyurethane PIVC dressing and optimal PIVC flushing, all in agreement with published reports 7,23,26,27 . In our study, the overall mean of dressing status was substantially higher for the intervention group compared to the control group at 12 months (66•86 [SD 17 •10] vs 51•37 [SD 25 •26]), a rate comparable to the 64 -79% of dressings in optimal conditions reported previously 13,23,28 .…”
Section: Discussionsupporting
confidence: 84%
“…To date, many studies using multimodal interventions have successfully reduced PIVC failure and complication rates, and the incidence of peripheral intravenous catheterrelated to bloodstream infections [6][7][8] . However, the results from these studies must be interpreted with caution due to, for example, their use of unrandomized or non-equivalent groups, or the conduct on single sites, which would limit the generalisability of the results.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is crucial for healthcare professionals to be aware of the factors that may lead to this condition, including several negativities, to understand how to manage it [7,8]. The guidelines available for peripheral intravenous insertion mainly focus on site selection and insertion, and there is a lack of established guidelines on how to recognize or manage DIVA [1,[9][10][11]. In this context, the present study was aimed to provide basic information regarding the risk factors for difficult peripheral intravenous cannulation and its management.…”
Section: Introductionmentioning
confidence: 99%
“…Peripheral intravenous catheters (PIVCs) are the most widely used intravenous treatment tools for hospitalized patients [1,2]. Previous studies have shown that PIVCs are administered to approximately 80% of inpatients for fluid supplementation, medication, blood transfusion, etc.…”
Section: Introductionmentioning
confidence: 99%
“…The PIVC fixation method normally proceeds as follows: (1) the PIVC and infusion tube are secured with tension-free dressing; (2) the dressing should be shaped based on the shape of the Y joint of the PIVC; (3) the dressing is pressed from the center to the edge; then, (4) using tape, and without applying too much pressure, the root of the extension line is fixed in an omega (Ω) shape.…”
Section: Introductionmentioning
confidence: 99%